Application Of A Flow-Through Triiodide Detector For The Rapid Determination Of Peroxide Value In Edible Oils. - Saad, Bahruddin; Wan, Tatt Wai; Boey, Peng Lim; Saleh, Muhammad Idiris (2006)
Lipid oxidation constitutes a major quality problem in the processing and storage of fats and oils, and is a major contributor to food deterioration.